Analysis of disposition (policy) and bureaucratic factors as an effort to accelerate stunting reduction in Binjai City In 2024 - Gea, Handerman Vitu (Institute Of Computer Science (IOCS), 2025)
Stunting is one of the public health problems in Indonesia that requires cross-sector interventions, including at the regional level. This study aims to analyze dispositional and bureaucratic factors in supporting the acceleration of stunting reduction in Binjai City, in accordance with the mandate of Presidential Regulation Number 72 of 2021. The research approach uses a mixed methods design, with quantitative stages through SPSS data analysis to identify factors related to the empowerment of the Family Assistance Team, and qualitative through interviews and observations to explore the supporting and inhibiting factors of policy implementation. The research sample consisted of 53 respondents, with 10 supporting informants from various local stakeholders. The results show that disposition variables, which include policy attitudes and implementation, as well as bureaucratic efficiency, have a significant influence on the success of empowering the Family Support Team in carrying out national priority tasks. This research confirms the importance of commitment and leadership roles in empowering subordinates and simplifying bureaucratic procedures to improve the effectiveness of public policies. The implication of these findings is the need to strengthen cross-sector coordination and community-based approaches to accelerate the achievement of stunting reduction targets at the local level.